Iles, frontières et migrations méditerranéennes : Lampedusa et les autres - Nathalie Bernardie-Tahir; Camille Schmoll (L'Espace Politique)
Introductory article of the issue 25 (2015-1) of the journal L’Espace politique entitled "Lampedusa, Mediterranean Islands, Borders and Migrations"